“COWOK BE GENTLE” : MASKULINITAS MAHASISWA LAKI-LAKI MUSLIM DI SURABAYA - Nur Wulan (Lakon : Jurnal Kajian Sastra dan Budaya, 2015)
This article discusses about ideal masculine norms perceived by University male Muslim students in Surabaya. There are two groups of male students interviewed in this research, namely students affiliated with the Dakwah movement and those who are not affiliated with the movement. The two groups share similar forms of ideal masculinity which are associated with restraint and maturity, not those related with muscularity and virility. This could be influenced by the contemplative and receptive dimension of Islam, as well as the paternalistic culture of Indonesian societies. It could be argued that restraint is an important feature of Indonesian masculinities.